2008
DOI: 10.5130/ijcre.v1i0.888
|View full text |Cite
|
Sign up to set email alerts
|

Breaking Out of the Local: International dimensions of science shops

Abstract: In this article we want to give an overview of the international dimension and the interest of the European Union (EU) in the concept of Science Shops. The European Commission (EC) manages the day-to-day business by initiating and implementing EU policies and spending EU funds. The EC support for Science Shops has been an important factor for the international interest and progress of the Science Shop movement. This article will not give detailed information about daily routines of a Science Shop. Detailed inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…In the 1980s, severe cutbacks in financial support from the French government heightened the precarious state of the existing Science Shops and eventually they were all forced to close their doors [Stewart, 1988]. It has become increasingly apparent that when governments and universities prioritise market-oriented knowledge transfer, they prefer to fund science parks and knowledge/technology transfer units, rather than science shops, which tend to be more concerned with the social impact and democratisation of science [DeBok and Steinhaus, 2008;Fischer, Leydesdorff and Schophaus, 2004;Vargiu, Cocco and Ghibellini, 2019;Wachelder, 2003;Urias et al, 2020]. However, Science Shops provide a balance in a context where more commercially oriented technology transfer and science parks are supported for economic reasons [Leydesdorff and Ward, 2005].…”
Section: Understanding the Context-based Dependency Of Science Shopsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the 1980s, severe cutbacks in financial support from the French government heightened the precarious state of the existing Science Shops and eventually they were all forced to close their doors [Stewart, 1988]. It has become increasingly apparent that when governments and universities prioritise market-oriented knowledge transfer, they prefer to fund science parks and knowledge/technology transfer units, rather than science shops, which tend to be more concerned with the social impact and democratisation of science [DeBok and Steinhaus, 2008;Fischer, Leydesdorff and Schophaus, 2004;Vargiu, Cocco and Ghibellini, 2019;Wachelder, 2003;Urias et al, 2020]. However, Science Shops provide a balance in a context where more commercially oriented technology transfer and science parks are supported for economic reasons [Leydesdorff and Ward, 2005].…”
Section: Understanding the Context-based Dependency Of Science Shopsmentioning
confidence: 99%
“…As Wachelder [2003] and Leydesdorff and Ward [2005] argue, the ability to adapt the model to these external changes is what will permit these structures to survive. Science shops, while maintaining their mission-driven commitment to solve societal problems, may have to rethink their focus and alliances on a regular basis to stay resilient [DeBok and Steinhaus, 2008], while upholding the social and public values from which they were initially born.…”
Section: Understanding the Context-based Dependency Of Science Shopsmentioning
confidence: 99%
“…The above refers to dealing with sustainability and continuity over time as being connected to factors that are intrinsic to the Science Shop itself. Literature on Science Shops (De Bok & Steinhaus 2008;Leydesdorff & Ward 2005;Wachelder 2003) maintains that such internal factors come to interplay with external ones to a relevant extent and determine organisations' durability. The Dutch experience is often reported in literature as paradigmatic (Farkas 1999).…”
Section: Overcoming Fragility and Ensuring The Durability Of Science mentioning
confidence: 99%
“…Science Shops emerged in The Netherlands in the 1970s, facilitated by a favourable political context that allowed university staff and students to start partnerships with civil society organizations (CSOs). Students, supervised by senior researchers, undertook research projects for free upon CSOs' requests 3,4 . In the 1980s, the Dutch Science Shop movement inspired other European countries.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9] Science Shops differ in the activities they conduct, how they are organized, in which context and fields they work, and how they operate. 4 However, although no dominant organizational structure defines a 'Science Shop', they all aim to respond to research topics identified and prioritized with a bottom-up approach. 1 Despite the growing interest, their role is currently relatively small as few Although participatory methods are increasingly used in research, most research today still addresses topics identified and prioritized by researchers and funders (public and private) that are not necessarily aligned with the research needs of a broader community of stakeholders (including citizens).…”
Section: Introductionmentioning
confidence: 99%